Divorce as a Performative Speech Act: A Cross-Cultural Study - Hashim Aliwey Mohammed Alhusseini, Asst. Prof.; Nawal Fadhil Abbas, Asst. Prof.; Ahmed Qadouri Abed, Asst. Prof. (Journal of College of Education, 2021)
The focus of this paper is to investigate whether the divorce act is one of the performative speech acts in English and Arabic cultures or not. The researchers assumed that what is regarded performative speech act in one culture might not be so in another. This assumption is applied to the divorce act in both English and Arab cultures. The researchers believe that divorce as a speech act underlies some pragmalinguistic differences in English and Arabic. To manipulate this argument, certain religious and legislative texts extracted from Arabic and English cultures are to be discussed to prove this assumption. To achieve the aim of this paper, the researchers adopt Austin’s (1962) interpretation of speech act theory and the concept of Felicity Conditions (FCs). Consequently, the goal of this study is to discuss and compare cross-culturally the divorce act in both languages to identify the similarities and differences between the two languages.